Respuesta :

Answer:

f(g(x))=1x^2 +-2x+1

Step-by-step explanation:

your inputs should be

1

-2

1

If f(x) = [tex]x^{2}[/tex], g(x) = [tex]x -1[/tex] then f(g(x)) = [tex]1x^{2} -2x+1[/tex].

What is a function?

Function, in mathematics, an expression, rule, or law that defines a relationship between one variable (the independent variable) and another variable (the dependent variable).

Given

f(x) = [tex]x^{2}[/tex]

g(x) = [tex]x -1[/tex]

f(g(x)) = [tex](x-1)^{2}[/tex]

It is in the form of [tex](a-b)^{2}=a^{2} -2(a)(b) +b^{2}[/tex]

= [tex]x^{2} -2(x)(1) +1^{2}[/tex]

= [tex]x^{2} -2x+1[/tex]

f(g(x)) = [tex]1x^{2} -2x+1[/tex]

Hence, If f(x) = [tex]x^{2}[/tex], g(x) = [tex]x -1[/tex] then f(g(x)) = [tex]1x^{2} -2x+1[/tex].

Find out more information about function here

https://brainly.com/question/14708913

#SPJ2